Sukapura Go Digital: Pemberdayaan UMKM, Kelompok Tani, dan Pelaku Wisata Melalui Pelatihan Digital Marketing dan Konten Kreatif di Desa Ngepung, Kec.Sukapura Kabupaten Probolinggo - Mohammad Rofiuddin (Universitas Islam Internasional Darullughah Wadda'wah, 2026)
Sukapura Village, Probolinggo Regency, holds significant economic potential as a buffer zone for Mount Bromo tourism; however, this potential remains underutilized due to low digital literacy among residents, weak UMKM product branding, and the lack of integration between the agricultural, micro-enterprise, and tourism sectors in a digital economic chain. The community service program